Opportunities and Challenges for Students in Learning Arabic Vocabulary in the Arabic Language Education Program at UINSI Samarinda - Jayanti, Annida Rida; Farhat, Muhammad Fathi; Hidayah, Annisa; Fatmawati, Nur; Rokhman, Muh Fatkhur; Norahmah, Asyifa; Mahfuuzhah, Raihaanah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
Vocabulary mastery is a fundamental aspect of Arabic language learning; however, students often encounter difficulties in memorizing and retaining new words, particularly abstract and religious vocabulary. This phenomenon affects their ability to read, write, and communicate effectively, highlighting the importance of understanding the strategies, challenges, and opportunities present in the higher education context. This study aims to explore the experiences of students in the Arabic Education Program at UINSI Samarinda regarding vocabulary memorization. A qualitative phenomenological approach was employed, with data collected through semi-structured interviews, participatory observation, and documentation of vocabulary assignments. Twelve active students were selected using purposive sampling, and interactive analysis techniques proposed by Miles, Huberman, and Saldana were applied. The findings indicate that students employ personal learning strategies such as regular repetition, flashcards, sentence construction, and vocabulary grouping to strengthen retention. Internal challenges include fluctuating motivation, mental fatigue, and difficulties with abstract vocabulary, whereas external challenges involve limited learning resources, insufficient speaking practice, and lack of interaction with native speakers. Students leverage learning opportunities through digital applications, online forums, and social collaboration to enhance vocabulary comprehension and retention. These findings underscore that successful vocabulary acquisition is influenced by the interaction of individual strategies, motivation, and socio-cultural context, demonstrating the effectiveness of integrating cognitive, social, and technological strategies. The study provides practical implications for the development of collaborative and digital-based vocabulary learning methods and emphasizes the significance of social context and student experiences in Arabic language education.